The Efforts of Social Services and Empowerment of Village Communities, Banyumas Regency in Managing People With Mental Disadvantages - Khasan, Agung Nur (UMPurwokerto Law Review, 2022)
Abstract Everyone has the right to get mental health protection, whether healthy, at-risk, or people with mental disorders. Problems arise when sufferers do not get good care, roaming the streets. The problem of people with mental disorders who are neglected in the Banyumas Regency has not been handled optimally. This study aims to determine the efforts of the Social Service and Village Community Empowerment of Banyumas Regency in dealing with People with Mental Disorders who are neglected on the road and to find out the obstacles experienced by the Banyumas Regency Social and Village Community Empowerment Service in dealing with people with mental disorders who are neglected. The method used is the normative juridical method. Interviews with related parties were conducted to complete secondary data. The results of the study indicate that the government, through the Department of Social and Village Community Empowerment in Banyumas Regency, has carried out management by providing handling and services to People with Mental Disorders who are neglected, homeless, threatening the safety of themselves and/or others and/or disturbing public order and/or security. But not optimal. There are two obstacles in the effort to implement these countermeasures, namely internal and external. Constraints are internal in nature, namely the distribution of personnel who assist in field operations and personnel who have not been balanced. In addition, there is a lack of participation from the surrounding community to report the presence of people with mental disorders who are homeless. Efforts to deal with people with mental disorders can be maximized if cooperation from the Social Service and Village Community Empowerment with the community. Keywords Management, Social Service, Mental Disorder. Abstrak Setiap orang berhak untuk mendapatkan pelindungan kesehatan jiwa, baik yang sehat, berisiko maupun Orang Dengan Gangguan Jiwa. Permasalahan muncul apabila penderita tidak mendapat perawatan yang baik sehingga berkeliaran di jalan-jalan. Permasalahan Orang Dengan Gangguan Jiwa yang terlantar di Kabupaten Banyumas belum tertangani secara maksimal. Penelitian ini bertujuan untuk mengetahui Upaya Dinas Sosial dan Pemberdayaan Masyarakat Desa Kabupaten Banyumas dalam penanggulangan Orang Dengan Gangguan Jiwa yang terlantar di jalan dan mengetahui kendala yang dialami Dinas Sosial dan Pemberdayaan Masyarakat Desa Kabupaten Banyumas dalam penanggulangan orang dengan gangguan jiwa yang terlantar. Metode yang digunakan adalah menggunakan metode yuridis normatif. Wawancara dengan pihak terkait dilakukan untuk melengkapi data sekunder. Hasil penelitian menunjukkan bahwa pemerintah melalui Dinas Sosial dan Pemberdayaan Masyarakat Desa Kabupaten Banyumas sudah melakukan penatalaksanaan dengan memberikan penanganan dan pelayanan terhadap Orang Dengan Gangguan Jiwa yang terlantar, menggelandang, mengancam keselamatan dirinya dan /atau orang lain dan/atau mengganggu ketertiban dan/atau keamanan umum, namun belum maksimal. Ada 2 kendala dalam upaya melaksanakan penanggulangan tersebut yaitu bersifat intern dan ektern. Kendala yang bersifat intern yaitu penyebaran tenaga yang membantu dalam operasi lapangan dan personil yang belum seimbang. Selain itu kurangnya partisipasi masyarakat sekitar untuk melaporkan adanya orang dengan gangguan jiwa yang menggelandang. Upaya Penanggulangan orang dengan gangguan jiwa bisa maksimal apabila ada kerjasama dari Dinas Sosial dan Pemberdayaan Masyarakat Desa dengan masyarakat. Kata kunci: manajemen, pelayanan sosial, kelainan jiwa.